The role of pH, temperature and catalyst type in caramel manufacturing process - Nor Shuhada, Shoberi (2010)

(untitled)
Caramel is a brown to black liquid or solid having the characteristic odor of burn sugar and a pleasant bitter taste. It is prepared by heat treatment of carbohydrate in a process called caramelization. The purpose of this study is to investigate the effect of temperature, pH, types of catalyst and also time taken to complete caramelization process for glucose. In this research, glucose was used to prepare two different classes of caramel (class III and class IV). Class III is prepared by adding ammonia to glucose and class IV by adding ammonia and sodium sulfite to glucose. Different preheating temperature ranged between (70-100)°C and different pH values ranged between (5-9) were investigated to find the optimum preheating temperature and pH values for caramelization reaction at 121°C. The prepared caramel was characterized by measuring its absorbance using UV-VIS spectrophotometer at wavelength 510 nm and 610 nm. The higher absorbance reading was at preheating temperature 100°C for both Ammonia and Ammonia Sulfite caramel. Result from the experiment showed that at alkaline condition, pH 8 give better results for both Ammonia and Ammonia Sulfite caramel compare to other pH. It also showed that Ammonia Sulfite caramel, at same condition with Ammonia caramel have darker color and higher absorbance reading.